Students' perceived predictors of an effective active learning/problem-based learning session: a pilot study. - Jacob, Sabrina A.; Khan, Tahir M.; Pusparajah, Priyia; Velu, Saraswati S.; Lee, Learn Han; Davey, Tamzyn M. (Journal of Pharmacy Practice & Research, 2016)
Active learning ( AL)/problem-based learning ( PBL) has been shown to improve the reasoning, communication and team-work skills of students. However, the success of AL/ PBL tends to vary depending on local context and culture. We undertook a study to assess pharmacy students' current experience, expectations and level of understanding of AL/ PBL. A focus group discussion involving ten Year-4 pharmacy students was conducted in Malaysia. Three key themes emerged: expectations of the AL/ PBL session, tutor characteristics and cultural issues. The students expected that the AL/ PBL session should help them apply their knowledge in real-life clinical situations. They also felt that the personality of the tutor was the key to the success of AL/ PBL, and that Asians were more hesitant to participate in AL/ PBL sessions. AL/ PBL has the potential to be effective provided the sessions are carefully planned, and tutors are well trained in the context of local culture.